The effect of sports on oral health in Riyadh city: A cross-sectional study - Abdulrahman Al Saffan; Rawan Marey Alshahry; Samar Abdulrahman Alrwissan; Zainab Abdulatif Aljanoubi; Raghad Abdulaziz Alswailem (Wolters Kluwer Medknow Publications, 2020)
Background: The global sports nutrition industry has skyrocketed regarding its total worth which has led to an enormous inflow of a variety of supplemental products. All of which are advertised to help the consumer achieve the desired body shape. The increased consumption of all sorts of protein and carbohydrates supplements have been reported to play a significant role in hastening dental decay. Materials and Methods: A cross-sectional study was conducted by the distribution of printed questionnaires among amateur bodybuilders/powerlifters in 13 gyms and fitness centers in addition to a 4-day event entitled "Fitness, healthy living and sports investment event". A total of 1314 men and women participated in completing the questionnaire. Results: The majority (60.5%) of the participants were males and non-smokers (62.0%). Most of the participants reported using nutritional supplements (73.1%). Nearly, half the participants reported the use of >7 nutritional supplements per week (48.6%). A statistically significant result was found in regards to the relationship between increased consumption of dietary supplements and poor oral health. The methods of oral hygiene reported, appear to be insufficient. Conclusion: It is evident that amateur weightlifters and bodybuilders are a new risk group for developing dental caries. Therefore, more attempts must be made to raise the awareness regarding the implications of increasing the consumption of carbohydrates, proteins and the sugary sports drinks on oral health, and the accompanied salivary dehydration during and after workouts, which may aggravate the decaying process.